2004
DOI: 10.1016/j.bbrc.2004.01.095
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 family gene modulation during spontaneous apoptosis of B-chronic lymphocytic leukemia cells

Abstract: Malignant cell accumulation in B-cell chronic lymphocytic leukemia (B-CLL) is primarily caused by defective apoptosis rather than increased proliferation. To further understand the role of Bcl-2 family members, known regulators of apoptosis, in the abnormal B-CLL survival, we have measured their mRNA levels in fresh B-CLL cells and in cultures undergoing spontaneous apoptosis. Using RNA protection assays we found constitutive expression of most bcl-2 members with high levels of bcl2, bcl-w, bad, bak, bax, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 23 publications
0
18
1
3
Order By: Relevance
“…The presence of this gene variant has been correlated with lower BAX transcript and protein levels in CLL cells (33,36), and in our study the rs11667351 variant, which is in linkage disequilibrium with rs4645878, was also associated with lower BAX mRNA levels in lymphocytes. The role of BAX in the CLL pathogenesis is not clear because CLL cells seem to have higher BAX levels than normal B lymphocytes (35). On the other hand, our observation of a protective effect for the G125A change on CLL risk is paradoxical with its apparent relationship with more advanced stage, treatment resistance, and short overall survival of CLL patients observed in some studies (36)(37)(38), suggesting a potential different role for this variant in the development and progression of the disease.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The presence of this gene variant has been correlated with lower BAX transcript and protein levels in CLL cells (33,36), and in our study the rs11667351 variant, which is in linkage disequilibrium with rs4645878, was also associated with lower BAX mRNA levels in lymphocytes. The role of BAX in the CLL pathogenesis is not clear because CLL cells seem to have higher BAX levels than normal B lymphocytes (35). On the other hand, our observation of a protective effect for the G125A change on CLL risk is paradoxical with its apparent relationship with more advanced stage, treatment resistance, and short overall survival of CLL patients observed in some studies (36)(37)(38), suggesting a potential different role for this variant in the development and progression of the disease.…”
Section: Discussioncontrasting
confidence: 56%
“…Several studies have evaluated the risk of CLL using a restricted number of genetic variants in a limited number of candidate genes, placed in the coding or in the putative promoter sequences (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). To date, only one study has published results of highthroughput genotyping to the study of CLL risk, analyzing a large number of nonsynonymous SNPs in 992 CLL patients and 2,707 controls (13).…”
Section: Discussionmentioning
confidence: 99%
“…It has been described that, in chronic lymphocytic leukemia cells, decreased Bcl-2/Bax ratios and conformational changes of Bax and Bak are among the early steps of spontaneous apoptosis initiation. 24,44 It has also been postulated that blasts in myelodysplastic syndromes express low levels of Bcl-2, which may facilitate the characteristic high levels of spontaneous apoptosis and inefficient hematopoiesis resulting in cytopenias. 45 Taken together, we suggest that the low Bcl-2/Bax ratio and the absence of Bcl-2 phosphorylation in G 1 cells are at least partly responsible for their high incidence of spontaneous and high susceptibility to ABT-737-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that continuous contact with CD40L is not a dominant factor in in vivo survival of circulating CLL cells. Sanz et al 45 found decreased levels of Bcl-2, Bfl-1 and Mcl-1 in CLL cells undergoing spontaneous apoptosis, which was not observed by us using a 4two-fold change in signal level as criterium for significance (see Figure 1 and Supplementary data). Possibly, results of the semiquantitative RNAse-protection approach can differ from the MLPA procedure when using RNA from apoptotic cells.…”
Section: Discussionmentioning
confidence: 99%